Prescriptions for Bedtime Sedatives After the Introduction of a General Admission Order Set at an Academic Health Center: The Potential and Pitfalls of Order Sets. Issue 4 (December 2017) - Kara, Areeba; Isaacs, Alex N.; Nisly, Sarah A.
Abstract : Objective: This study describes the impact of modifications to a general admission order set on physician prescribing of 2 as-needed or pro re nata (PRN) bedtime sedatives. Methods: The hospitalists at our institution have used a general medical admission order set since 2005. Zolpidem was the only as-needed (PRN) bedtime sedative option on the order set until trazodone was added in December 2008. Trazodone is preferred over zolpidem in the geriatric population. We identified patients admitted by the hospitalists between January 2007 and August 2013 who were prescribed with either zolpidem or trazodone as a PRN sedative. Patient demographics, date and time of the order, and number of sedative doses administered during the hospitalization were recorded. Orders placed within 12 hours of admission were attributed to admission orders. Results: Between 2007 and 2013, the number of patients admitted by the hospitalists with an order for PRN trazodone on admission increased by 18-fold. During the same period, the number of admissions by the hospitalists increased by 2.3 times. Zolpidem orders exceeded those for trazodone in all age groups until 2008. After the addition of trazodone, its use exceeded that of zolpidem. Almost half (48%) of all patients did not have a dose of the PRN trazodone administered. Conclusions: Although order sets can be leveraged to align practitioners with established guidelines, the expediency of using medications on an order set may overcome physicians' clinical judgment. The content of an order set therefore deserves careful scrutiny before implementation. Abstract : Supplemental digital content is available in the text.